Konflik dan Klaim Pengelolaan Kawasan Hutan Jati di Muna - La Ode Topo Jers (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This research studies the conflict between the society and government about the mastery and claim over the teak forest in forest areas of Kontu, Patu-Patu, Lasukara, and surrounding areas. This research was conducted in the Regency of Muna Southeast Sulawesi by using a qualitative approach with the ethnographic method. The finding of the research revealed that the the presence of conflict because of the attraction between the two interests with the society about the government's lack of clarity of the status of forest area. There were two interpretations that attract each other which about protected forest areas between the government and the society on behalf of indigenous groups. The government claimed that the mastery over Kontu forest area, Patu-Patu and its surroundings as a state based on formal law. While the communities that living around the forest claimed that forest areas were their heritage that based on unwritten customary law. Government in claiming an area utilized a wide variety of state power and equipment, while the indigenous groups rely solely on the strength of arguments that were historical, so there was no force that supports people to defend their rights. Keywords: teak forest, area claim, conflict, society, government